Combined Tuberculosis of the Larynx and Lungs in a Tender-age Infant - Tatiana I. Danilko; Ekaterina S. Hohrina; Olga K. Kiselevich; Anna N. Yusubova (Педиатрическая фармакология, 2025)
Background. Tuberculosis in tender-age infants remains a serious and urgent problem due to the immaturity of the immune system, the lack of a specific clinical picture in the early stages of infection, difficulties in the differential diagnosis of X-ray signs of the disease and anatomical and physiological characteristics of the body. It is important that children from the group of close bacillary contact have a higher risk of developing the disease during the first years of life, especially in the absence of preventive treatment and dynamic monitoring.Case report. A case report of combined tuberculosis of the larynx and lungs in a child born to a mother with tuberculosis and who did not receive preventive therapy is presented. During the first year of life, the patient was repeatedly treated in the infectious diseases department of the city hospital with the diagnosis: “Sublingular laryngitis, laryngeal stenosis” — without improvement. Based on the ineffectiveness of the treatment and the deterioration of the patient’s condition, a chest examination was performed. Laryngeal microlaryngoscopy was performed, Mycobacterium tuberculosis complex DNA was detected in the biopsy materials by polymerase chain reaction. According to the conducted studies, at the age of 1 year and 3 months, a diagnosis was made: “Tuberculosis of multiple localizations: miliary tuberculosis of the lungs. Tuberculosis of the intrathoracic lymph nodes of all groups on the left, paratracheal group on the right, bifurcation group, infiltration phase with calcification elements. Tuberculosis of the larynx. Without isolation of Mycobacterium tuberculosis”. A full course of anti-tuberculosis therapy was performed.Conclusion. The presented case report clearly showed the lack of preventive antituberculosis measures, which led to infection and subsequent late diagnosis of widespread tuberculosis in a tender-age infant.